2016
DOI: 10.1158/2159-8290.cd-15-1227
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Meta-Analyses of Breast, Ovarian, and Prostate Cancer Association Studies Identify Multiple New Susceptibility Loci Shared by at Least Two Cancer Types

Abstract: Breast, ovarian, and prostate cancers are hormone-related and may have a shared genetic basis, but this has not been investigated systematically by genome-wide association (GWA) studies. Meta-analyses combining the largest GWA meta-analysis data sets for these cancers totaling 112,349 cases and 116,421 controls of European ancestry, all together and in pairs, identifi ed at P < 10 −8 seven new cross-cancer loci: three associated with susceptibility to all three cancers (rs17041869/2q13/ BCL2L11 ; rs7937840/11q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 80 publications
10
152
2
3
Order By: Relevance
“…Eighteen of these risk loci are associated with all and/or serous OC, five are associated with MOC risk, one is associated with ENOC, and one is associated with CCOC, exemplifying the genetic heterogeneity by histotype. In addition, a large-scale pooled analysis of genome-wide association studies of ovarian, breast, and prostate cancers identified five novel loci 81 . The identified common risk alleles account for approximately 4% of the polygenic risk in the European population and, taken together with high risk alleles, explain 40% of the heritability 82 .…”
Section: Genetic Epidemiologymentioning
confidence: 99%
“…Eighteen of these risk loci are associated with all and/or serous OC, five are associated with MOC risk, one is associated with ENOC, and one is associated with CCOC, exemplifying the genetic heterogeneity by histotype. In addition, a large-scale pooled analysis of genome-wide association studies of ovarian, breast, and prostate cancers identified five novel loci 81 . The identified common risk alleles account for approximately 4% of the polygenic risk in the European population and, taken together with high risk alleles, explain 40% of the heritability 82 .…”
Section: Genetic Epidemiologymentioning
confidence: 99%
“…This indicates how integrating several data sources with OmicsNPC allows to retrieve findings that would not be identified by analyzing each omics dataset in isolation. Interestingly, an enrichment analysis performed on these 24 genes over the Disease Ontology of the OBO Foundry [46] shows that six out of the ten most enriched diseases are ovarian-related cancers (Table 1), a class of malignancies known to share similar hormonal [47] and genetic bases [48] with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…From the 92 published BC-associated SNPs in 24 , only 51 SNPs existed in our SNP discovery set in both KBCP and OBCS sample sets. Recently, Michailidou et al .…”
Section: Experimental Set-upsmentioning
confidence: 99%
“…We compared the proposed approach with a system trained on 51 known BC-associated SNPs 24,25 , a PRS-derived model and a number of conventional machine learning methods already used in GWAS to identify disease-associated SNPs. We then investigated the predictive potential of the identified SNPs in classifying ER status.…”
Section: Introductionmentioning
confidence: 99%